Minority education's influence on Yi language use of Yi people in Xichang city - Tang Ye; Soon, Chiow Thai (Asian Journal of Research in Education and Social Sciences, 2024)
There are 55 ethnic minorities in China, and the Yi are the sixth largest ethnic minority in China. The Yi in Sichuan mainly live in the Liangshan Yi Autonomous Prefecture, which is the largest Yi autonomous region in China. Xichang City, the state capital, is home to a large population of mixed Yi and Han Chinese. The Yi have their own language (Yi language) and script (Yi script), but the use of the Yi language is not favorable. The number of Yi students who do not know any Yi at all is gradually increasing as a proportion of their age, and more and more Yi youths are not learning Yi. This is not conducive to the use and protection of the Yi language. In this study, we focus on the implementation of local minority education policies, especially bilingual education. The researcher discovered a discrepancy between the outcomes and objectives of the bilingual education policy, resulting in inadequate implementation. This, in turn, leads to a cognitive bias among students and teachers towards bilingual education, thereby impacting the use and transmission of the Yi language.